2018
DOI: 10.1101/287656
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy and acceptability of non-invasive brain stimulation for the treatment of adult unipolar and bipolar depression: A systematic review and meta-analysis of randomised sham-controlled trials

Abstract: 26We examined the efficacy and acceptability of non-invasive brain stimulation in adult 27 unipolar and bipolar depression. Randomised sham-controlled trials of transcranial direct 28 current stimulation (tDCS), transcranial magnetic stimulation (TMS) and theta-burst 29 stimulation (TBS), without co-initiation of another treatment, were included. We analysed 30 response, remission and all-cause discontinuation rates, and depression severity scores. Fifty-31 four studies were included (N = 2,959, mean age = 44.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 54 publications
1
32
0
4
Order By: Relevance
“…Interestingly, the present tRNS trial and Colleen K Loo et al (2018) have used the highest total number of sessions and strongest stimulation parameters, including current intensity, compared to other investigations of the antidepressant effects of transcranial electrical stimulation (Blumberger et al, 2012;Colleen K Loo et al, 2012;U Palm et al, 2012;Andre R Brunoni et al, 2013a;Bennabi et al, 2015), with both studies reporting no advantage of active stimulation over sham. Overall, studies show tDCS has antidepressant efficacy (Mutz et al, 2018), though one study suggested this may be less than escitalopram (Andre R Brunoni et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the present tRNS trial and Colleen K Loo et al (2018) have used the highest total number of sessions and strongest stimulation parameters, including current intensity, compared to other investigations of the antidepressant effects of transcranial electrical stimulation (Blumberger et al, 2012;Colleen K Loo et al, 2012;U Palm et al, 2012;Andre R Brunoni et al, 2013a;Bennabi et al, 2015), with both studies reporting no advantage of active stimulation over sham. Overall, studies show tDCS has antidepressant efficacy (Mutz et al, 2018), though one study suggested this may be less than escitalopram (Andre R Brunoni et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Applying a direct current between the electrodes, referred to as transcranial direct current stimulation (tDCS), has been demonstrated to have antidepressant effects in clinical trials (Colleen K Loo et al, 2012;Andre R Brunoni et al, 2013a;Andre R Brunoni et al, 2017). Recent meta-analyses of randomised, sham-controlled trials have found tDCS to be more effective than sham stimulation, with significantly higher remission and response rates as well as a greater reduction in depressive symptoms (André R. Brunoni et al, 2016;Mutz et al, 2018). As depression has increasingly been conceptualised as a disorder underpinned by disrupted neuroplasticity (Pittenger and Duman, 2008;Liu et al, 2017), cumulative changes to synaptic functioning may underlie the therapeutic effects observed in clinical trials of tDCS (Szymkowicz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…8 Nonetheless, tDCS has produced mixed outcomes in terms of antidepressant efficacy. [9][10][11][12] This may reflect a heterogeneous likelihood of response across participants. Therefore, identifying predictors of response may provide useful insights into tDCS, such as clarifying its mechanisms of action, predicting treatment outcomes, and designing better-tailored trials within the framework of precision psychiatry.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Transcranial Magnetic Stimulation has proven to be efficacious at alleviating depression symptoms over a wide range of settings particularly for treatment-resistant cases of MDD. [6][7][8][9][10][11][12] The technology is widely utilized in clinical practice but the practical application to ethnically, financially, and geographically diverse patient groups with complex comorbidities require further characterization. [13][14][15] We recently examined the effectiveness of rTMS in combination with cognitive behavioral therapy (CBT) in the treatment of MDD using data derived from a retrospective review of medical records from patients with MDD undergoing rTMS therapy at a suburban tertiary psychiatric clinic, AwakeningsKC Clinical Neuroscience Institute (CNI).…”
Section: Introductionmentioning
confidence: 99%